2012
DOI: 10.1182/blood-2012-03-417139
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of heparan sulfate 2-O-sulfotransferase accentuates neutrophil infiltration during acute inflammation in mice

Abstract: Neutrophil recruitment and extravasation at sites of inflammation provide a mechanism for host defense. We showed previously that heparan sulfate, a type of sulfated glycosaminoglycan, facilitates neutrophil recruitment based on the reduction of neutrophil infiltration in mice in which the overall sulfation of the chains was reduced by selective inactivation of IntroductionThe inflammatory response, initiated by injury or infection, begins by release of cytokines, such as TNF-␣ and IL-1, from resident macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 52 publications
2
72
0
Order By: Relevance
“…Again, this binding may be modified by chemical editing of HS chains. For example, changing the domain structure of HS by inactivation of Hs2st (which causes a compensatory increase in glucosamine N-sulfation and 6-Osulfation) results in enhanced binding of IL-8 to the endothelium and increases inflammation (5).…”
Section: Function Of the Renal Endothelial Glycocalyxmentioning
confidence: 99%
“…Again, this binding may be modified by chemical editing of HS chains. For example, changing the domain structure of HS by inactivation of Hs2st (which causes a compensatory increase in glucosamine N-sulfation and 6-Osulfation) results in enhanced binding of IL-8 to the endothelium and increases inflammation (5).…”
Section: Function Of the Renal Endothelial Glycocalyxmentioning
confidence: 99%
“…The assembly of heparan sulfate in these and other cells is not template driven; rather, it is thought to depend on the organization and specificity of biosynthetic enzymes and the availability of precursors. Thus, 2-O sulfotransferase deficiency not only reduces heparan sulfate 2-O-sulfation, but also strongly enhances N-sulfation and moderately elevates 6-Osulfation by an unknown compensatory mechanism (Axelsson et al, 2012). These secondary biosynthetic effects lead to complex changes in the heparan sulfate domain structure and overall heparan sulfate sulfation in these cells.…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophmentioning
confidence: 99%
“…Analysis of these animals revealed that neutrophil-derived HS plays a significant role in controlling bactericidal activity. Whereas inactivation of Hs2st on endothelial cells facilitates neutrophil infiltration to sterile inflammatory stimuli (11), the impaired intrinsic bactericidal activity of Hs2st-deficient neutrophils results in increased susceptibility of Hs2st-deficient mice to invasive bacterial infection. The bactericidal defect in Hs2st-deficient mice correlates with reduced NET formation and altered histone affinity to HS within the NETs.…”
mentioning
confidence: 99%
“…HS modulates the rapid recruitment of neutrophils to sites of infection or injury at different levels, in particular through its interactions with cytokines, chemokines, and selectins (8). We reported previously that reduced expression and altered sulfation of HS on endothelial cells, achieved by inactivating glucosamine N-deacetylase-N-sulfotransferase-1 (Ndst1) or uronyl 2-O-sulfotransferase (Hs2st), altered neutrophil extravasation to sites of sterile inflammation by modifying interactions between endothelial HS and L-selectins on neutrophils and chemokines released during the inflammatory response (11,12). In contrast, the same modifications of HS on the neutrophil cell surface did not affect trafficking during sterile inflammation (11,12) and had only mild effects on the acquired immune responses (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation